Hubungan Asupan Fe Dan Aktivitas Fisik Dengan Kejadian Dismenore Primer Pada Remaja Putri di SMA Dan SMK Batik Surakarta - Nita Hasri Wulandari; Endang Nur Widiyaningsih (JGK:Jurnal Gizi dan Kesehatan, 2023)
Background: The prevalence of dysmenorrhea in Central Java isisquitehigh 56% and in Surakarta it exceeds the prevalence of Central Java by 89.8%. This is caused by several factors including, psychological, individual, blockage in the cervicalcanal, female reproductive organs, endocrine, allergies and nutritional intake. Another factor that causes primary dysmenorrhea is lack of physical activity. Based on a preliminary study conductedon 131 female SMA and SMK Batik Surakarta, it was found that 80.15% of female student sex perienced primary dysmenorrhea. So this research was conducted to determine the relation ship between Fe intake and physical activity with the incidence of primary dysmenorrhea in young women at SMA and SMK Batik Surakarta. Objective: This study aims to determine the relation ship between Fe intake and physical activity with the incidence of primary dysmenorrhea in female adolescentsat Batik High Schooland Surakarta vocational school. Method: This type of research is observational with a cross-sectional approach. The sampling technique eused simple random sampling with a total sampleof 192 respondents. Data on the incidence of dysmenorrhea were obtainedusing WaLIDDScore. Fe intake data were obtainedusing Semi-Quantitative Food Frequency (SQ-FFQ). Physicalactivity data were obtainedusingthe International Physical Activity Questionnaire (IPAQ). Data analysis using chi-square. Results: A total of 91.7% of the sample experienced primary dysmenorrhea. Samples with a Fe intake of less than 65.1%. Samples with mild physical activity were 35.9%. Statistical analysis results between Fe intake and the occurrence of primary dysmenorrhea showed a valueof p-value=0.003 and between physical activity and the occurrence of primary dysmenorrhea showed a valueof p-value=0.003. Conclusion: There is a relationship between Fe intake and physical activity with the occurrence of primary dysmenorrhea.